Prevalência de malnutrição num serviço de Medicina Interna - Rego, Almerindo (1994)
The nutritional assessment was made to 444 patients, with the average age of 51 and all interned in the medicine service of the Hospital of Angra, using anthropometric and biochemical parameters. The anthropometric parameters used were the skinfold thickness and the mid-upper arm circumference, and the biochemical ones were the plasmatic albumin and transferrin. The global prevalence of malnutrition was 55%, the moderate malnutrition was 48.7% and the se vere malnutrition was 6,3%. Marasmos was prevalent (36%). Neoplastic diseases, cerebrovascular diseases and chronic obstructive lung disease, chronic alcoholism and chronic renal failure, were the most frequently connected pathologies.